Primary splenic histiocytic sarcoma associated with hemophagocytic lymphohistiocytosis: A case report and review of literature of next‐generation sequencing involving FLT3, NOTCH2, and KMT2A mutations. Issue 5 (22nd July 2021) - Montalvo, Nelson; Lara‐Endara, Jorge; Redrobán, Ligia; Leiva, María; Armijos, Christian; Russo, Leonardo
Abstract: Background: Histiocytic sarcoma is a very rare monocyte/macrophage‐derived hematopoietic system tumor with a poor prognosis whose diagnosis is pathologically challenging due to its extreme rarity and histological overlap with various mimicking entities in which histiocytes also predominate. Case: We report the case of a 33‐year‐old male patient with hemophagocytic lymphohistiocytosis, purpuric syndrome, and significant splenomegaly. The patient underwent splenectomy; subsequent macroscopic examination revealed a spleen weighing 2065 grams with hyperemic red pulp and multiple infarcts at the periphery. The histological and immunohistochemical study established a diagnosis of primary splenic histiocytic sarcoma with frequent hemophagocytosis. Next‐generation sequencing demonstrated mutations in FLT3, NOTCH2, and KMT2A, microsatellite stability, and a tumor mutational burden of 2 mut/Mb. The patient's condition deteriorated clinically from the appearance of the first symptoms and he died 6 months later from multi‐organ failure. Conclusion: Primary splenic histiocytic sarcoma is one of the rarest tumors of the hematopoietic system. We report the first case with mutations in FLT3, NOTCH2, and KMT2A, and associated hemophagocytic lymphohistiocytosis.